Pengaruh Pemberian Ekstrak Etanol Kulit Batang Faloak (sterculia sp.) Terhadap Penurunan Kadar Glukoasa Darah Yang Diinduksi Glukosa - Stefany S.A Fernandez; Elisabia Edel (JURNAL INFO KESEHATAN, 2017)
Diabetes mellitus is an abnormality of carbohydrate metabolism caused by elevated blood glucose levels characterized by frequent polyuria, multiple polyphagia, and polidipsi (much to drink). Previous research has shown that plants containing flavonoids have a hypoglycemic activity or are capable of causing a decrease in blood glucose levels and are protected against damage to β cells as an insulin-producing and may increase insulin sensitivity. The aim of this research is to know whether Faloak bark ethanol extract (Sterculia sp.) Has an antidiabetic effect on male rats induced with 50% glucose solution. Extraction method used in this research is the maceration method using ethanol 96%. The test animals used were 20 mice divided into five treatment groups. The treatment group consisted of positive control of metformin 65 mg / kg BW, negative control of 1% Na CMC and extract at dose 150 mg / KgBB, 300 mg / KgBB and 600 mg / kgBW. Glucose levels are measured every 30 minutes for 2 hours. Data were analyzed using ANOVA. This study showed that ethanol extract from the bark of faloak (Sterculia sp) at doses of 150 mg / kgBW, 300mg / KgBB, 600mg / KgBB may affect the decrease in blood glucose in animals induced by glucose.